UJI DAYA PREDASI Forficula sp. (Dermaptera : Forficulidae) dan Dolichoderus sp. (Hymenoptera : Formicidae) TERHADAP HAMA PERUSAK PUCUK KELAPA Brontispa Longissima Gestro (Coleoptera : Chrysomelidae) di LABORATORIUM - Dona Monica Br Bangun; Syahrial Oemry; Mukhtar Iskandar Pinem (Universitas Sumatera Utara, 2015)
Coressponding author : E-mail : bangundona@ymail.comABSTRACTResearch on title the predation ability of Forficula sp. (Dermaptera : Forficulidae) andDolichoderus sp. (Hymenoptera : Formicidae) of Brontispa Longissima Gestro.(Coleoptera : Chrysomelidae) in laboratory aimed to study the predation ability of Forficula sp.and Dolichoderus sp. of Brontispa longissima Gestro (Coleoptera : Chrysomelidae) in Laboratory.The experiment design was randomized complete design with 8 treatments and 3 replications.The tested treatment were larvae and imago of B. longissima, 2 Forficula sp, 2 Dolichoderus sp,1 Forficula sp and 1 Dolichoderus sp on 10 larvaes/stoples and 2 Forficula sp, 2 Dolichoderus sp,1 Forficula sp and 1 Dolichoderus sp on 10 imagoes/stoples with. The result showed thatpercentage of mortality and the predators behavior. The results showed that the highest percentageof mortality on P1 (2 Forficula sp. on 10 larvaes/stoples) was 96.67% and the lowest onP01 (larvae control) was 0% and the result showed that Forficula sp. prey mechanism begins withthe introduction of active antenna movement then using forcep (cerci) captureBrontispa longissima Gestro and predator prey Dolichoderus sp. way starts with the runningapproaching pest predators and prey circling approach as the larvae begins to feed through the bodysurface.Keywords : predation, B. longissima Gestro, percentage mortality